2008
DOI: 10.1080/09638280701400730
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from the personal insights of individuals living and coping with Multiple Sclerosis?

Abstract: The most salient finding is that there is a need for a formal approach to the management of psychosocial problems and challenges associated with MS. This will require both users and health professionals working together to further the development of clinical guidelines and services for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 25 publications
11
142
0
2
Order By: Relevance
“…The MS guidance (NICE 2014) incorporates qualitative studies, but while none define self-management, collectively they describe implicit expectations that patients devise their own mechanisms for 'going away and living with it' (e.g. Malcomson et al 2008). More recent qualitative studies have identified a lack of ongoing provision to support self-management (Deibel et al 2013) and shown how people with MS often receive generic rather than tailored information and education (Chaplin et al 2012).…”
Section: Self-managementmentioning
confidence: 99%
“…The MS guidance (NICE 2014) incorporates qualitative studies, but while none define self-management, collectively they describe implicit expectations that patients devise their own mechanisms for 'going away and living with it' (e.g. Malcomson et al 2008). More recent qualitative studies have identified a lack of ongoing provision to support self-management (Deibel et al 2013) and shown how people with MS often receive generic rather than tailored information and education (Chaplin et al 2012).…”
Section: Self-managementmentioning
confidence: 99%
“…Informational support is an important aspect of healthcare delivery for people with MS. Low levels of perceived provision of information is associated with distress and dissatisfaction with healthcare services [20]. A large qualitative study by Gulick [43], reported low levels of perceived informational support in both male and female participants with MS. As informational support was the 2 nd most provided support sub-type across the included studies, it suggests a great improvement in the provision of information for MS participants over the last 20 years.…”
Section: Benefi Ts Attributable To Social Supportmentioning
confidence: 99%
“…This can help reduce levels of distress amongst participants [20] during intervention sessions. Information, involving training sessions with the telerehabilitation technologies, should be constantly accessible to participants.…”
Section: Recommendations On the Use Of Informational Support To Incrementioning
confidence: 99%
See 1 more Smart Citation
“…Other impacts identified were effects on sexual relationships (57%), effects on choice of career (51%) and 52% reported effects on long-term personal friendships and relationships. 37 In another study, Malcomson et al 38 conducted two qualitative focus group discussions to explore the impact of multiple sclerosis (MS) (n = 13, age 40 -67 years, mean disease duration = 17 years) on patients' lives. Several patients reported changes to their employment circumstances along with other disease-related impacts (interpersonal and social life, stress, unpredictability, fear and impact on daily living).…”
Section: Job and Career Choicementioning
confidence: 99%